2007
DOI: 10.1097/aud.0b013e31812f7185
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Integration and Lipreading Abilities of Older Adults with Normal and Impaired Hearing

Abstract: Overall, the results of the current study suggest that despite increased reliance on visual speech information, older adults who have hearing impairment do not exhibit better V speech perception or auditory-visual integration than age-matched individuals who have normal hearing. These findings indicate that inclusion of V and AV speech perception measures can provide important information for designing maximally effective audiological rehabilitation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
142
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 25 publications
14
142
2
1
Order By: Relevance
“…9 We concluded, as did Cienkowski and Carney 8 in an earlier study, that age affects one's ability to lip-read (ie, to recognize speech using only the visual signal) but does not affect one's ability to integrate. Similarly, Tye-Murray et al 9 compared integration enhancement of a group of older participants with age-appropriate hearing loss to a group of older participants with normal hearing and found no difference in their integration abilities.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…9 We concluded, as did Cienkowski and Carney 8 in an earlier study, that age affects one's ability to lip-read (ie, to recognize speech using only the visual signal) but does not affect one's ability to integrate. Similarly, Tye-Murray et al 9 compared integration enhancement of a group of older participants with age-appropriate hearing loss to a group of older participants with normal hearing and found no difference in their integration abilities.…”
mentioning
confidence: 66%
“…The findings from both Sommers et al 3 and TyeMurray et al 9 have led us to reconceptualize how receivers might combine the auditory and visual speech signals. Perhaps there are no differences between older and younger persons' abilities to combine A and V information and no difference between older normal-hearing and hearing-impaired persons' abilities because there is no distinct integration stage as depicted in Figure 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent data suggest that hearing impairment in older adults is not necessarily associated with better AV integration abilities (Tye-Murray et al 2007). Here, we show degraded AV integration in older adults with HL relative to NHs in the same age group.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Tye-Murray et al (2007) showed that older adults with mild HL could achieve levels of accuracy equal to those of NH controls for audiovisual (AV) speech perception in noise. Although this study is well founded and much needed, additional studies are needed to determine the variance and replicability of these results, especially in more typical listening environments.…”
Section: Introductionmentioning
confidence: 99%